A bibliometric systematic review of extracellular vesicles in cutaneous malignant melanoma from 2005 to 2025 - Christodoulides, Natasha; Bollard, Stephanie; Chabria, Yashna; O’Driscoll, Lorraine; Potter, Shirley (Frontiers in Oncology, 2026)
IntroductionCutaneous melanoma (CM) is among the most aggressive human malignancies characterised by its strong propensity for metastasis. Recent advances in melanoma research have reframed the disease as a systemic condition driven by dynamic interactions between tumour cells, the tumour microenvironment and the immune system. Increasing evidence indicates that these interactions are largely mediated by extracellular vesicles (EVs), small lipid-bilayer-enclosed particles that facilitate intercellular communication. EVs can be isolated from all biofluids, making them attractive minimally invasive biomarkers for diagnosis, staging, monitoring response to treatment and predicting relapse. Despite growing interest, a comprehensive overview of global research trends in this area is lacking.MethodsWe performed a bibliometric systematic review of EVs-related CM research from 2005 to 2025 using Web of Science, Scopus, and EMBASE. Eligible studies focused on EVs characterisation, biomarker development, and functional roles in melanoma. Data were analysed using the Bibliometrix R-package to assess publication trends, citation metrics, author networks, institutional output and thematic evolution.ResultsAn analysis of the 288 included studies revealed that publication activity peaked in 2020, representing a 4000% increase in annual output compared to 2005. Additionally, a marked surge in citation frequency was observed beginning in 2018. The United States and China led in output, although international collaboration was limited. Chongqing Medical University and the University of Pittsburgh were among the most productive institutions. The Journal of Extracellular Vesicles published the highest number of articles in this field. Keyword and co-citation analysis identified major research themes, including immune evasion, biomarker discovery, and therapy resistance.DiscussionThis first bibliometric analysis of EV research in CM reveals a rapidly expanding field with evolving research priorities. These findings offer a data-driven framework to guide future studies, promote collaboration, and inform strategic investment in EVs-based melanoma research.